2014
DOI: 10.1111/ene.12425
|View full text |Cite
|
Sign up to set email alerts
|

Association of moyamoya disease with thyroid autoantibodies and thyroid function: a case−control study and meta‐analysis

Abstract: Evidence strongly suggests that elevated thyroid autoantibodies and elevated thyroid function are independently associated with MMD. These clinical variables may require regular monitoring in patients with MMD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 14 publications
1
22
0
Order By: Relevance
“…A recent study of patients with MMD reported a high incidence of elevated thyroid function and thyroid autoantibody levels. 2) 13) Thyrotoxicosis may be the trigger of the vascular attack in MMD patients that results in the increase in sympathetic nervous system sensitivity. 9) Choi et al have reported about coronary vasospasms with thyrotoxicosis in 6,923 subjects; they showed that the hyperthyroid state enhances the sensitivity of the vascular contractile responses to either norepinephrine (NE) or 5-hydroxytryptamine (5-HT).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study of patients with MMD reported a high incidence of elevated thyroid function and thyroid autoantibody levels. 2) 13) Thyrotoxicosis may be the trigger of the vascular attack in MMD patients that results in the increase in sympathetic nervous system sensitivity. 9) Choi et al have reported about coronary vasospasms with thyrotoxicosis in 6,923 subjects; they showed that the hyperthyroid state enhances the sensitivity of the vascular contractile responses to either norepinephrine (NE) or 5-hydroxytryptamine (5-HT).…”
Section: Discussionmentioning
confidence: 99%
“…The association of GD and intracranial occlusive arteriopathy, complicated with ischemic strokes, is increasingly being reported in the scientific literature. [5][6][7] The pathogenesis has not been elucidated yet, but the association does not seem to be coincidental. The genetic association in GD is more well established than the genetic association in Moyamoya disease;…”
Section: Discussionmentioning
confidence: 99%
“…Li et al 3) also demonstrated higher level of thyroid autoantibodies and thyroid function in pediatric MMD. A recent meta-analysis 8) showed that elevated thyroid autoantibodies (OR: 8.77; P < 0.001) and thyroid function (OR: 9.74; P = 0.003) were significantly associated with MMD development after reviewing two adults and one pediatric MMD studies. 7 9) Nevertheless, heterogeneity among studies such as patients’ age and inclusion criteria could be concerns to the interpretation.…”
Section: Introductionmentioning
confidence: 99%